Analisis Kebutuhan Pengunjung terhadap Sarana dan Parsarana di Daya Tarik Wisata Pantai Hamadi, Kota Jayapura, Papua - Angela Tangfo; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
Hamadi beach is one of the leading tourist attractions located right in the Hamadi village and has become a top priority for visitors to the Capital of Papua Province every weekend, especially on Saturdays / Sundays and other holidays with the main purpose for recreation. However on the other hand its lack of tourism infrastructure dan substructure, due to unopotimal management system. The objectives of this study are (1) to determine the condition of tourism infrasubstructure and substrucutre in Hamadi Jayapura, Papua, (2) to determine the needs of visitors for tourism infrastructure and substructure that need to be provided in the tourist attraction of Hamadi Beach, Jayapura, Papua.The types of data used in this study are qualitative and quantitative data. Sources of data used in this study include primary and secondary data. Data collection techniques carried out by observation, interviews, library research, questionnaires, and documentation. Sample determination is obtained by quota sampling and analyzed using qualitative descriptive statistical analysis using a Likert Scale measurement tool and Importance Performance Analysis. The results showed that, Hamadi beach is still lack of tourism tourism tourism infrastructure. Visitors also need infrastructure and substructure to be provided ini the tourism attraction site area, security posts, accommodation, souvenir shops, rest area, children play ground etc. Keywords Tourist Attraction, Visitors Needs, Tourism Infrastructure and Substructure